Agricultural extension staff need innovative training programmes - Zinnah, Moses (Technical Centre for Agricultural and Rural Cooperation, 1997)
a pilot BSc Agricultural Extension programme designed for mid-career agricultural extension staff was launched in November 1993 at the University of Cape Coast, Ghana